2023
DOI: 10.3389/fcimb.2023.1110787
|View full text |Cite
|
Sign up to set email alerts
|

The implication of gut microbiota in recovery from gastrointestinal surgery

Abstract: Recovery from gastrointestinal (GI) surgery is often interrupted by the unpredictable occurrence of postoperative complications, including infections, anastomotic leak, GI dysmotility, malabsorption, cancer development, and cancer recurrence, in which the implication of gut microbiota is beginning to emerge. Gut microbiota can be imbalanced before surgery due to the underlying disease and its treatment. The immediate preparations for GI surgery, including fasting, mechanical bowel cleaning, and antibiotic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 136 publications
0
5
0
Order By: Relevance
“…Recent studies have suggested that Prevotellaceae could be associated with intestinal inflammation (Elinav et al , 2011). Lachnospiraceae plays a vital role in reducing oxidative stress and preventing inflammation (Zhang et al , 2023). It has been proposed that the Lactobacillaceae mixture improved intestinal health in mice with Type 2 diabetes by alleviating inflammation in the gut (Li et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that Prevotellaceae could be associated with intestinal inflammation (Elinav et al , 2011). Lachnospiraceae plays a vital role in reducing oxidative stress and preventing inflammation (Zhang et al , 2023). It has been proposed that the Lactobacillaceae mixture improved intestinal health in mice with Type 2 diabetes by alleviating inflammation in the gut (Li et al , 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that Prevotellaceae could be associated with intestinal inflammation (Elinav et al, 2011). Lachnospiraceae plays a vital role in reducing oxidative stress and preventing inflammation (Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between intestinal flora and wound recovery following CRC surgery is a subject of growing importance, especially considering the increase in surgical interventions for CRC and the critical role that the gut microbiota plays in overall health. 21 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of cancer, surgery is commonly used as a treatment method and significantly impacts patient microbiota, especially the gut microbiota 196 . Research has shown that in patients undergoing tumor surgery, the use of preoperative antibiotics may lead to a reduction in gut microbial diversity and the growth of pathogenic bacteria, potentially resulting in complications such as increased gut permeability 197 , 198 . Modulating the gut microbiota can be considered a potential strategy to alleviate this issue.…”
Section: Questioning the Impact Of The Gut Microbiota On Cancer Treat...mentioning
confidence: 99%